(untitled) (Journal of Rangpur Medical College, 2025)
Introduction: Middle ear cancers are rare but aggressive tumors with a poor outlook due to late diagnosis and complicated anatomy. It is essential to correlate radiologic findings with pathologic details for accurate staging, effective surgical planning, and optimal outcomes. Objective: This study aimed to examine the link between radiologic and pathologic data in middle ear cancers and their effect on early detection and surgical choices. Methods: We conducted a prospective study involving 100 patients with confirmed middle ear cancers, conducted at Rajshahi Medical College, Rajshahi, Bangladesh, from January 2024 to December 2024. We performed high-resolution computed tomography (CT) and magnetic resonance imaging (MRI) of the temporal bone, focusing on bone erosion, mastoid involvement, petrous apex involvement, and intracranial spread. The pathologic evaluation included histologic type, perineural invasion, lymph vascular invasion, and margin status. Data were analyzed using SPSS v26.0 to calculate Pearson correlation coefficients to measure the agreement between radiologic and pathologic findings. Results: The study included 56% males with an average age of 51.2 years. Squamous cell carcinoma was the most common histologic type (62%). We found strong correlations between intracranial extension and dural/brain invasion (r=0.88), bone erosion and histologic bone invasion (r=0.82), and mastoid involvement with pathologic mastoid invasion (r=0.79). Radiologic findings changed the surgical plan in 34% of cases, with 78% achieving local control and 81% surviving for one year. Conclusion: The strong links between radiologic and pathologic findings in middle ear cancers ensure accurate preoperative staging and surgical planning, leading to better local control and survival outcomes. High-resolution imaging is crucial for effective management strategies. J Rang Med Col. 2025 Sep;10(2): 90-96